2020
DOI: 10.1161/jaha.120.016615
|View full text |Cite
|
Sign up to set email alerts
|

AKAP12 Signaling Complex: Impacts of Compartmentalizing cAMP‐Dependent Signaling Pathways in the Heart and Various Signaling Systems

Abstract: Abstract Heart failure is a complex clinical syndrome, represented as an impairment in ventricular filling and myocardial blood ejection. As such, heart failure is one of the leading causes of death in the United States. With a mortality rate of 1 per 8 individuals and a prevalence of 6.2 million Americans, it has been projected that heart failure prevalence will increase by 46% by 2030. Cardiac remodeling (a general determinant of heart fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 120 publications
0
24
0
Order By: Relevance
“…A-kinase anchor protein 12 (AKAP12)/Src-suppressed C-kinase substrate (SSeCKS) is a member of the AKAP family and a component of the cytoskeleton structure [ 1 ]. AKAP12 maintains the stability of cells and tissues, and regulates cell proliferation and metastasis through activation of the phosphoinositide 3-kinase (PI3K)/protein kinase B (AKT) or protein kinase A (PKA)/protein kinase C (PKC) pathways [ [1] , [2] , [3] , [4] ].…”
Section: Introductionmentioning
confidence: 99%
“…A-kinase anchor protein 12 (AKAP12)/Src-suppressed C-kinase substrate (SSeCKS) is a member of the AKAP family and a component of the cytoskeleton structure [ 1 ]. AKAP12 maintains the stability of cells and tissues, and regulates cell proliferation and metastasis through activation of the phosphoinositide 3-kinase (PI3K)/protein kinase B (AKT) or protein kinase A (PKA)/protein kinase C (PKC) pathways [ [1] , [2] , [3] , [4] ].…”
Section: Introductionmentioning
confidence: 99%
“…A-Kinase Anchoring Protein 12 (AKAP12) is a structurally diverse protein that shares common features to bind the protein kinase A regulatory subunit (Qasim and McConnell, 2020;Seo et al, 2021). Previous studies have suggested that AKAP12 plays a potential role in male germ cells and ovarian granulosa cells in mammals (Erlichman et al, 1999;Binder et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Akap12 is particularly associated with bringing components of the Protein Kinase A (PKA) signaling cascade to the cell membrane, suggesting a role for PKA signaling in early endothelial cell-mediated inflammation. 47…”
Section: Resultsmentioning
confidence: 99%